Pharmacokinetics, pharmacodynamics, and safety of verinurad with and without allopurinol in healthy Asian, Chinese, and non‐Asian participants. Issue 3 (20th May 2022) - Johansson, Susanne; Han, David; Hunt, Thomas; Björck, Karin; Florica, Delia; Gillen, Michael; Hall, Jesse; Erlandsson, Fredrik
Abstract: Verinurad is a selective inhibitor of uric acid transporter 1 (URAT1). Here, we assessed the safety, pharmacokinetics, and pharmacodynamics of verinurad + allopurinol and verinurad monotherapy in healthy participants. Studies 1 (NCT03836599) and 2 (NCT02608710) were randomized Phase 1 studies. In Study 1, 12 healthy Asian participants received 24 mg verinurad + 300 mg allopurinol or placebo, and 9 healthy Chinese participants received 12 mg verinurad + 300 mg allopurinol. In Study 2, 24 healthy non‐Asian male participants received 12 mg verinurad. Safety analyses included assessment of adverse events (AEs). Pharmacokinetic parameters included maximum concentration (Cmax ) and area under plasma concentration‐time curve (AUC) over 24 h (AUCτ ). Pharmacodynamic parameters included percentage change from baseline (day –1) in serum uric acid (sUA) and urinary uric acid (uUA). There were no serious AEs or deaths in either study. In Study 1, steady‐state geometric mean (gCV%) Cmax and AUCτ values of verinurad after 7 days' dosing were 73.6 (29.0) ng/mL and 478 (18.4) ng·h/mL, respectively, in healthy Asian participants, and 42.0 (40.1) ng/mL and 264 (36.1) ng·h/mL, respectively, in healthy Chinese participants; in Study 2, gCV% values were 36.3 (36.5) ng/mL and 271 (31.0) ng·h/mL, respectively. sUA decreased and uUA excretion increased compared with baseline following verinurad + allopurinol (Study 1) or verinurad (Study 2). When accounting for dose, the steady‐state pharmacokinetics of verinurad following multiple dosing were comparable between healthy Asian and Chinese participants and healthy non‐Asian participants. Verinurad treatments were well tolerated, including at higher verinurad exposures than previously evaluated after repeated dosing. Abstract :